Experimental evaluation of value of friction coefficient in the drawbead region - Trzepieciński, Tomasz; Fejkiel, Romuald; Kubit, Andrzej (Advances in Mechanical and Materials Engineering, 2018)
Drawbeads are supposed to change the stress state of sheets in specific areas of the sheet material, or compensate for material flow at the periphery of the drawpiece, especially when forming complex shaped thin-walled products. The article presents the results of frictional resistance testing of a DC04 steel sheet using a drawbead simulator test. Experimental investigations were carried out using a special device that allows a change in the degree of deformation of the sheet metal on the drawbead. Specimens were tested for: (i) three degrees of sheet deformation; (ii) three countersamples’ surface roughness; and (iii) three lubrication conditions: dry friction, machine oil lubrication and paint lubrication. The test specimens were cut out along, and transversely to, the direction of rolling of the sheet metal. The basic relations between technological parameters of friction test and coefficient of friction were determined.